1998
DOI: 10.1136/bmj.317.7156.437
|View full text |Cite
|
Sign up to set email alerts
|

Mother to child transmission of hepatitis C virus: prospective study of risk factors and timing of infection in children born to women seronegative for HIV-1

Abstract: Results: 13 of the 403 children had acquired hepatitis C virus infection at the end of follow up. All these children were born to women positive for hepatitis C virus RNA; none of the 128 RNA negative mothers passed on the infection (difference 5%, 95% confidence interval 2% to 7%). 6 children had viral RNA immediately after birth. 111 women had used intravenous drugs and 20 had received blood transfusions. 11 of the infected children were born to these women compared with 2 to the 144 with no known risk facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
178
3
10

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 274 publications
(212 citation statements)
references
References 19 publications
(18 reference statements)
21
178
3
10
Order By: Relevance
“…[33][34][35]38 Other studies do not confirm this finding. 15,27,28,30 Moreover, in some of the studies indicating increased risk with vaginal delivery, the difference fell short of statistical significance, including a large European study where mode of delivery was known for 1,400 infants. 24 Elective Cesarean section may confer some protection, but emergency Cesarean section does not.…”
Section: Factors Correlating With Mother-to-infant Transmission Of Hcvmentioning
confidence: 99%
See 2 more Smart Citations
“…[33][34][35]38 Other studies do not confirm this finding. 15,27,28,30 Moreover, in some of the studies indicating increased risk with vaginal delivery, the difference fell short of statistical significance, including a large European study where mode of delivery was known for 1,400 infants. 24 Elective Cesarean section may confer some protection, but emergency Cesarean section does not.…”
Section: Factors Correlating With Mother-to-infant Transmission Of Hcvmentioning
confidence: 99%
“…In one study, pre-term delivery was quantitatively higher among anti-HCV positive women, but the difference was not statistically significant. 15 In the same series, Boxall, 1994 66 3,522 0.14 N/A Ohto, 1994 30 7,698 0.68 58 Marranconi, 1994 67 5,672 0.7 N/A Moriya, 1995 31 16,714 0.98 53 Zanetti, 1995 36 21,516 1.2 55 Manzini, 1995 68 5,000 0.7 ϳ70% Resti, 1998 27 25,654 the rate of Cesarean section was twice as high among anti-HCV positive women compared with the anti-HCV negative control group (statistically significant difference, P ϭ .004), and this higher rate was attributed in part to the policy of the investigators not to use fetal scalp blood sampling for fetal surveillance when fetal heart rate is abnormal in anti-HCV positive women.…”
Section: Issues Relating To Pregnancy and Chronic Hepatitis Cmentioning
confidence: 99%
See 1 more Smart Citation
“…Likely risk factors include perinatal practices (fetal scalp monitoring and caesarean‐section delivery), extended exposure to maternal blood, high levels of HCV viremia during pregnancy, and co‐infection with human immunodeficiency virus (HIV) 15, 16, 17, 18, 19. Although some studies have challenged several of these assumptions,20, 21 a recent meta‐analysis concluded that maternal HIV co‐infection is the most important determinant of the risk of perinatal transmission 15…”
Section: Epidemiologymentioning
confidence: 99%
“…Both intrauterine and intrapartum infection probably occur, but the relative contribution of each is uncertain. However, approximately one-third of neonates are HCV-viraemic at birth suggesting acquisition in utero [192].…”
Section: Hepatitis C Virusmentioning
confidence: 99%